Mawād Qirāʼiyyah Mubtakarah Qāʼimah ʿAlá Mahārat al-Tafkīr al-ʿUlyā Wafq Taṣnīf Bārit [Innovative Reading Materials Based on Higher Order Thinking Skills (HOTS) Aligned with Barrett’s Taxonomy] - Maisaroh, Siti; Sutaman, Sutaman; Ibrahim, Faishal Mahmoud Adam (Center of Language Development, Institut Agama Islam Negeri Madura, 2024)
In many Islamic universities, Arabic language instruction remains focused on memorization and low-level comprehension, limiting students’ ability to engage with texts critically. The lack of contextualized materials and limited use of interactive strategies have further contributed to low student motivation and superficial understanding. Addressing these challenges, this study aims to design and implement an instructional unit based on Higher-Order Thinking Skills (HOTS) for teaching Arabic reading comprehension to third-year students at an Islamic University in Madura. The study adopts a research and development (R&D) methodology using the ADDIE model, which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through interviews, classroom observations, document analysis, and pre- and post-tests to assess the impact of the instructional unit. Findings revealed significant improvements in students’ analytical and interpretive reading abilities and increased classroom participation. Expert evaluations confirmed the material’s validity, with an overall score of 89%. Integrating local cultural context and interactive technologies enhanced students’ motivation and engagement. The study highlights the importance of embedding HOTS into Arabic instruction to foster critical literacy and recommends applying this model to other language skills in both local and global learning environments.